Data as art - Toothman, J. J. (O'Reilly Media, 2011)
"Artistic visualizations and infographics tell the stories of rich data in unique, compelling ways and synthesize datasets in order to allow them to be interpreted, absorbed, and experienced in ways beyond the spreadsheet, pie chart, and bar graph."--Resource description page.